1991
DOI: 10.1093/fampra/8.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Care of the Dying: A Questionnaire Survey of General Practice Attenders

Abstract: In order to determine the views of General Practice attenders on death and dying, a survey was conducted using a questionnaire with nine questions on aspects of death and dying. There were 4117 respondents with an average age of 36.4 years, who attended 10 general practices. A control group of 100 patients was employed. There was a stated preference for management by the General Practitioner and a wish to die in the home. An honest approach by doctors was called for and the greatest fear concerning death was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…surgeries who had close experience of death and dying, reported a slightly lower home preference Nineteen studies were identified that reported (52% compared to 64%) and a higher preference preferences for place of care in advanced illness for hospice care (35%, compared to 16%) 10 comor at death. Fried et al 6 considered preferences pared with other attendees at these surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…surgeries who had close experience of death and dying, reported a slightly lower home preference Nineteen studies were identified that reported (52% compared to 64%) and a higher preference preferences for place of care in advanced illness for hospice care (35%, compared to 16%) 10 comor at death. Fried et al 6 considered preferences pared with other attendees at these surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…Negative perceptions about death and dying may manifest as fears and anxieties about the dying process, fears over lack of control at end-of-life, lack of openness between close family members when a person is dying, and behaviours associated with accessing palliative and end of life care services. [18][19][20][21][22] Nevertheless, public opinion surveys in both the UK and Ireland have shown that the public perceives there to be insufficient conversation about death and dying in the community 8,[23][24] and the majority would welcome discussions with clinicians in advance about end of life issues. 9,25 Modification of public perceptions of palliative care is central to improving knowledge of and access to services, empowering individuals, and involving communities in palliative and end of life care.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that over half of advanced cancer patients prefer to stay at home and die there [1, 5,6,18,27]. Moreover, some claimed that home-based services are cheaper than and as effective as hospital services [2,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%